ANALISIS PENGARUH ISU HUBUNGAN PEMERINTAH INDONESIA DENGAN PERUSAHAAN MOBIL LISTRIK TESLA TERRHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PT. VALE INDONESIA TBK - Windy Raharusun; Juanita R. Horman (INTAN Jurnal Penelitian Tambang, 2021)
This study aims to see the effect of the issue on the stock price of a nickel mining company, namely PT. Vale Indonesia Tbk. The total research time is 33 days with seven days of event period and 26 days of estimation period. The method used in this research is the event study method with the research variables are abnormal returns and trading volume activity. From the descriptive result, both abnormal return and trading volume activity affect the issue that can be seen with the mean value after the issue which is higher than the mean value before the issue. However, in the paired sample test, the two research variables yield different significance values. The abnormal return t value is -0.901 smaller than the t table of 0.4124 with a significance of 0.382, so the issue does not affect abnormal returns. The t trading volume activity is -2.305 higher than t table of 1.753 with a significance of 0.036, so the issue affects trading volume activity.